Struktura, igra in interpretacija - prispevek k historiatu koncepta "French Theory" - Šporer, David (Slavistična revija, 2020)
Confrontation of the fundamental models of interpretation in Jacques Derrida's early works is analysed as the pivotal point for future construction of the "postmodern literary theory". By the same token this points, just as French authors do with the term "French theory", to the concept's inextricable ties with French mediation of the European tradition in humanities within the framework of the reception of structuralism in the US.
Keywords: Derrida, Jacques; interpretacija; kritika metafizike; postmoderna literarna teorija; poststrukturalizem; recepcija; strukturalizem